(untitled) (Bangladesh Heart Journal, 2018)
Background: A substantial number of patients get admitted in different hospitals of Bangladesh with the diagnosis of acute coronary syndrome (ACS). No underlying conventional risk factors can be identified in significant number of these patients. Therefore new emerging risk factors are likely to be involved in these patients. As many authors reported that high serum ferritin levels are associated with diabetes mellitus (DM) and hypertension (HTN), it may have role in the pathogenesis of ACS.So we designed this study to test the relation between hyperferritinemia and newly diagnosed acute coronary syndrome patients of Bangladesh. Methods: The study was an observational case control study done in Department of Cardiology, Dhaka Medical College Hospital, from January 2013 to December 2013. Newly diagnosed patients with acute coronary syndrome (ACS) in the age group of 30- 70 years, admitted in the coronary care unit (CCU) of Dhaka Medical College Hospital, Dhaka, within the study period were taken as cases and age& sex matched healthy subject with no history of ischemic heart disease (IHD) and with normal ECG were taken as control by purposive sampling. In our study, the number of cases and controls were 65 each. So, total number of subject was 130. Results: According to the serum ferritin level both cases and controls were divided into two sub groups: subjects with normal ferritin level and with hyperferritinaemia. Normal ferritin level was found in 35(53.8%) subjects of case group and 62(95.4%) subjects of control groups. Hyperferritinaemia was found in 30(46.2%) subjects of case group and 3(4.6%) subjects of control group. Hyperferritinaemia was found to be significantly higher in case group than in control group (p<0.001). Conclusion: The study concludes that the serum ferritin level of patients with ACS was significantly higher than the control group. Bangladesh Heart Journal 2017; 32(2) : 89-93